Betulinic acid modulates urethane-induced genotoxicity and mutagenicity in mice and Drosophila melanogaster. (April 2020) - Oliveira, Victor Constante; Naves, Maria Paula Carvalho; de Morais, Cássio Resende; Constante, Sarah Alves Rodrigues; Orsolin, Priscila Capelari; Alves, Bianca Silva; Rinaldi Neto, Francisco; da Silva, Lucas Henrique Domingos; de Oliveira, Lucas Teixeira Souza; Ferreira, Natália Helen; Esperandim, Tábata Rodrigues; Cunha, Wilson Roberto; et al.
Abstract: Betulinic acid (BA) is a pentacyclic triterpenoid found in several plant species. Urethane (URE) is a known promutagen. Here, we examine the genotoxicity and mutagenicity of BA alone or in combination with URE using the bone marrow micronucleus assay in mice bone marrow cells and the Somatic Mutation and Recombination Test in Drosophila melanogaster . Findings revealed that BA alone was not genotoxic, but reduced the frequency of micronucleus when compared to the positive control. No significant differences were observed in the cytotoxicity. Biochemical analyzes showed no significant differences for liver (AST and ALT) or renal (creatinine and urea) function parameters, indicating the absence of hepatotoxic and nephrotoxic effects. BA alone did not increase the frequency of mutant spots, but reduced the total frequency of mutant spots when co-administered with URE in both ST and HB crosses. In addition, BA reduced the recombinogenic effect of URE at the highest concentrations of both crosses. In conclusion, under experimental conditions, BA has modulatory effects on the genotoxicity induced by URE in mice, as well as in somatic cells of D. melanogaster . We suggest that the modulatory effects of BA may be mainly due to its antioxidant and apoptotic properties. Highlights: BA was not toxic neither genotoxic to mice. BA has modulatory effects on the genotoxicity induced by URE in mice. BA was not toxic neither mutagenic to D. melanogaster. BA has modulatory effects on the mutagenicity induced by URE in somatic cells of Drosophila. Modulatory effects of BA may be due to its antioxidant and apoptotic properties.